2016
DOI: 10.1016/j.imbio.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A cell wall protein-based vaccine candidate induce protective immune response against Sporothrix schenckii infection

Abstract: Sporotrichosis is a subcutaneous mycosis caused by several closely related thermo-dimorphic fungi of the Sporothrix schenckii species complex, affecting humans and other mammals. In the last few years, new strategies have been proposed for controlling sporotrichosis owning to concerns about its growing incidence in humans, cats, and dogs in Brazil, as well as the toxicity and limited efficacy of conventional antifungal drugs. In this study, we assessed the immunogenicity and protective properties of two alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 40 publications
1
52
0
6
Order By: Relevance
“…Studies to identify a vaccine candidate and the ideal adjuvant are ongoing [40,43]. Promising results using S .…”
Section: Vaccine Candidates and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies to identify a vaccine candidate and the ideal adjuvant are ongoing [40,43]. Promising results using S .…”
Section: Vaccine Candidates and Perspectivesmentioning
confidence: 99%
“…Promising results using S . schenckii cell wall protein in an aluminum hydroxide (AH) adjuvanted formulation have been reported [43]. However, the use of AH as an adjuvant should be carefully reviewed for future studies in cats, since this compound is involved in feline vaccine-induced sarcomas [44].…”
Section: Vaccine Candidates and Perspectivesmentioning
confidence: 99%
“…In vitro assays with yeast cells opsonized with serum from immunized animals increased phagocytosis and inhibited the adhesion of the fungi to the fibroblasts [192]. …”
Section: Vaccine Development Against Fungal Diseasesmentioning
confidence: 99%
“…15 We also showed that the passive transference of sera from mice immunized with Al(OH) 3adjuvanted S. schenckii cell-wall proteins can induce protection in a subsequent challenge with the fungus. 16 The innate recognition of pathogens by pattern recognition receptors (PRRs) shapes the following adaptive immune response, so playing a critical role in determining the outcome of the infection. 17 To prevent pathogen invasion, PRRs survey the intracellular and extracellular space and play a critical role in the innate immune response by recognizing pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs).…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…More recently, we showed that S. schenckii systemic mouse infection induces the development of a protective Th17 response, featuring both Th17 and Th17/Th1 cells and the augmented ex vivo release of interleukin‐17 (IL‐17) and IL‐22 . We also showed that the passive transference of sera from mice immunized with Al(OH) 3 ‐adjuvanted S. schenckii cell‐wall proteins can induce protection in a subsequent challenge with the fungus …”
Section: Introductionmentioning
confidence: 99%